Efektivitas Penggunaan Media Pembelajaran Aplikasi Canva Dalam Meningkatkan Hasil Belajar Siswa MA Ibitidaussalam - Darwis, Darwis; Atmono, Dwi; Ratumbuysang, Monry Frack Nicky Gillian; Hasanah, Mahmudah (Jurnal Pendidikan Ekonomi (JUPE), 2024)
The use of learning media at MA Ibtidaussalam still uses conventional media so that it affects student learning outcomes. This study aims to determine the effectiveness of using Canva application learning media in improving student learning outcomes at MA Ibtidaussalam. The method used in this study is a quasi-experimental method. In the quasi-experimental method, this study used a Nonequivalent Control Group Design consisting of two groups, namely the experimental group and the control group. The research subjects consisted of 45 students divided into class XI IPS 1 (21 students) and XI IPS 2 (24 students). Data collection techniques use observation, learning outcomes tests, and documentation. Data analysis was carried out using normality test, homogeneity test and hypothesis test. The results showed that the use of Canva application learning media was able to improve the learning outcomes of grade XI social studies students. Based on the significance value, it can be concluded that there is a difference in the average student learning outcomes between the use of Canva application learning media and the use of conventional media. In addition, the results of the N-Gain score test show that the use of the Canva application is effective. This research indicates that the use of the Canva application as a learning medium can be an effective alternative to improve student learning outcomes at the high school level.